Physical, chemical, and microbiological stability test of liquid neurogenic Secretome at temperature 0-4°C and 20-25°C - Pamuji, Dimas Aditya Wahyu; Suroto, Heri; Soesilawati, Pratiwi; Utomo, Budi (Edelweiss Applied Science and Technology, 2024)
Nerve tissue is vital for motor, sensory, and autonomic activities, and peripheral neuropathy is a common disorder. Trauma causes 2-3% of peripheral nerve damage, with radial and plexus injuries being the most prevalent. Sciatic, peroneal, and tibial nerves are most impacted in 18-35-year-olds and 8% of 55-year-olds have peripheral neuropathy. Tissue engineering, including secretome studies, may be useful. This study aims to assess the stability of liquid neurogenic secretome at different temperatures by evaluating its physical, chemical, and microbiological properties. This in vitro experimental laboratory study employed a post-test only group design to compare the stability of liquid neurogenic secretome stored at temperatures of 0-40°C and 20-25°C, both on the first day and after 30 days. Stability was assessed through physical, chemical, and microbiological tests. Brain-derived neurotrophic factor (BDNF) concentration was similar in the room and refrigerator groups, indicating neurogenic secretome stability. Additionally, no bacterial growth was observed from day 1 to day 30, suggesting the secretome's resistance to contamination under both storage conditions. The secretome from purified mesenchymal stem cell (MSCs) along with antibiotics was effective in clearing clearing methicillin-resistant staphylococcus aureus (MRSA) biofilms in a mouse wound model and showed promise in treating multidrug-resistant chronic wound infections in a clinical trial involving dogs. This study provides insights into the physical, chemical, and microbiological stability of liquid neurogenic secretome under different storage conditions, highlighting its potential for therapeutic use.